Accuracy of Trauma on Scene Triage Screening Tool (Shock Index, Reverse Shock Index Glasgow Coma Scale and National Early Warning Score) to Predict the Severity of Emergency Department Triage: A Retrospective Cross-Sectional Study - Yuksen C; Angkoontassaneeyarat C; Thananupappaisal S; Laksanamapune T; Phontabtim M; Namsanor P (Open Access Emergency Medicine, 2023)
Chaiyaporn Yuksen, Chuenruthai Angkoontassaneeyarat, Sorawat Thananupappaisal, Thanakorn Laksanamapune, Malivan Phontabtim, Pamorn Namsanor Department of Emergency Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Chuenruthai Angkoontassaneeyarat, Department of Emergency Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, 270 Rama VI Road, Thung Phaya Thai, Ratchathewi, Bangkok, 10400, Thailand, Email chuenruthai.ang@gmail.comIntroduction: Prehospital trauma care includes on-scene assessments, essential treatment, and facilitating transfer to an appropriate trauma center to deliver optimal care for trauma patients. While the Simple Triage and Rapid Treatment (START), Revised Triage Sieve (rTS), and National Early Warning Score (NEWS) tools are user-friendly in a prehospital setting, there is currently no standardized on-scene triage protocol in Thailand Emergency Medical Service (EMS). Therefore, this study aims to evaluate the precision of these tools (SI, rSIG, and NEWS) in predicting the severity of trauma patients who are transferred to the emergency department (ED).Methods: This study was a retrospective cross-sectional and diagnostic research conducted on trauma patients transferred by EMS to the ED of Ramathibodi Hospital, a university-affiliated super tertiary care hospital in Bangkok, Thailand, from January 2015 to September 2022. We compared the on-scene triage tool (SI, rSIG, and NEWS) and ED triage tool (Emergency Severity Index) parameters, massive transfusion protocol (MTP), and intensive care unit (ICU) admission with the area under ROC (univariable analysis) and diagnostic odds ratio (multivariable logistic regression analysis). The optimal cut-off threshold for the best parameter was determined by selecting the value that produced the highest area under the ROC curve.Results: A total of 218 patients were traumatic patients transported by EMS to the ED, out of which 161 were classified as ESI levels 1– 2, while the remaining 57 patients were categorized as levels 3– 5 on the ESI triage scale. We found that NEWS was a more accurate triage tool to discriminate the severity of trauma patients than rSIG and SI. The area under the ROC was 0.74 (95% CI 0.70– 0.79) (OR 18.98, 95% CI 1.06– 337.25), 0.65 (95% CI 0.59– 0.70) (OR 1.74, 95% CI 0.17– 18.09) and 0.58 (95% CI 0.52– 0.65) (OR 0.28, 95% CI 0.04– 1.62), respectively (P-value < 0.001). The cut point of NEWS to discriminate ESI levels 1– 2 and levels 3– 5 was > 6 points.Conclusion: NEWS is the best on-scene triage screening tool to predict the severity at the emergency department, massive transfusion protocol (MTP), and intensive care unit (ICU) admission compared with other triage tools SI and rSIG.Keywords: triage, prehospital care, emergency medical services, emergency departments, trauma severity index